Rat cytomegalovirus genome scaffold and A033 gene as infection marker in rats - Camalxaman, Siti Nazrina (2013)
A local preliminary study has documented the prevalence of rat cytomegalovirus (RCMV) in the wild population to be as high as 96%. Hence, periodic screening and surveillance of laboratory rats is vital, since they may also harbor the viral agent, posing challenges for experimental usage. The lack of sequence information in RCMV ALL-03 strain however, has impeded its detection and prevented its assesment in vitro. This thesis describes the reactivation of RCMV ALL-03 from predilected sites, the establishment of rat brain endothelial cells (RBEC) as alternative target cells for viral replication and the identification of cross-reactive viral proteins with human CMV (HCMV). In addition, the draft genome for RCMV ALL-03 was generated using Next Generation Sequencing technology and assembled using CLC Genomics Workbench. This has led to the identification, analysis and primer design for the A033 gene, an infection determinant in RCMV. RCMV ALL-03 was reactivated from the brain, salivary gland and uterus of infected tissues and identified based on morphologic criteria classical of herpesvirus. RBEC primary cells were successfully established and deemed receptive for RCMV ALL-03 with concomitant production of plaques following cytopathogenic studies. Preliminary serological screening of HCMV in Selangor and Kuala Lumpur revealed 92% endemicity. Protein profiles of RCMV ALL-03 were compared to a local RCMV strain (RCMV UPM/Sg) and RCMV-E (Rat2; ATCC CRL-1764™) reference strain, revealing eight common protein bands in the range of 44-231 kDa. The detection of a 61-68 kDa cross reactive protein by Western Blot raises the possibility of an immunological cross-reactivity between RCMV and HCMV. The RCMV ALL-03 draft genome was sequenced alongside RCMV-E, generating six contigs for RCMV ALL-03 and 11 contigs for RCMV-E. The sizes of RCMV ALL-03 and RCMV-E draft genome sequences were ~198,895 bp and ~175,071 bp respectively, with a total of 136 genes for RCMV ALL-03 as opposed to 112 genes for RCMV-E. From this, only 46 genes were annotated for RCMV ALL-03 and 43 genes in RCMV-E. This includes the A033 gene, identified as gene 21 (1,173 bp) in RCMV ALL-03 and gene 20 (1,187 bp) in RCMV-E. Specific primer for the A033 gene, a marker for RCMV infection has been proposed, and its specificity validated using PCR against other viral strains. To conclude, this study confirms that RCMV ALL-03 is endotheliotropic, justifying its use as an alternative cell culture system that could be further exploited to study the effects of cellular activation of RCMV in the brain. Furthermore, this study addresses the lack of sequence information in RCMV ALL-03, by reporting the first draft of the genome, providing new genomic data acquisition which has not been disclosed to date. Primers for the A033 gene is being proposed to replace existing ones that were rendered non-specific, paving way towards the establishment of a more accurate and sensitive detection assay to screen for RCMV. Once completed, the genome sequence could be further developed as a recombinant vector for delivering human chimeric or antifertility genes.